HERBAL DRUGS IN PEDIATRIC RHINOSINUSITS TREATMENT - L. S. Titarova; D.P. Polyakov (Вопросы современной педиатрии, 2014)
The article referred to the use of herbal drugs in treatment of acute rhinosinusitis in children. Topical aspects of the etiology, pathogenesis, clinical manifestations and diagnosis of acute rhinosinusitis in children are disscussed. The advantages of application of herbal drugs in such pathology are discussed indications for these drugs and possible side effects. The results of research of the efficacy and safety of herbal drugs for the treatment and prevention of acute sinusitis in children are adduced.